(untitled) - Sunny Chaudhary; V Abdusamad; Aman Verma; Varun Garg; R K Siddharth; Vivek Singh (Asian Journal of Medical Research, 2020)
Chronic foot pain in pediatric age group is less common. The usual differential diagnosis may vary from musculoskeletal injury to serious diseases such as osteomyelitis. Benign bone tumor such as osteoid osteoma of foot is exceedingly rare in this age group. Here we present a rare case of osteoid osteoma of cuboid mimicking osteomyelitis. Patient was managed conservatively by Non-steroidal Anti-inflammatory drugs (NSAIDs) with good clinical outcome. Osteoid osteoma of foot bones should be kept in mind in cases with normal blood parameters.